Enzyme Mimic Nanomaterials and Their Biomedical Applications. (22nd April 2020) - Shang, Yingxu; Liu, Fengsong; Wang, Yuanning; Li, Na; Ding, Baoquan
Abstract: Nanomaterials with enzyme‐mimicking behavior (nanozymes) have attracted a lot of research interest recently. In comparison to natural enzymes, nanozymes hold many advantages, such as good stability, ease of production and surface functionalization. As the catalytic mechanism of nanozymes is gradually revealed, the application fields of nanozymes are also broadly explored. Beyond traditional colorimetric detection assays, nanozymes have been found to hold great potential in a variety of biomedical fields, such as tumor theranostics, antibacterial, antioxidation and bioorthogonal reactions. In this review, we summarize nanozymes consisting of different nanomaterials. In addition, we focus on the catalytic performance of nanozymes in biomedical applications. The prospects and challenges in the practical use of nanozymes are discussed at the end of this Minireview. Abstract : Nanozymes have attracted a lot of research interest and are gradually finding their way to a variety of applications. Herein, we review recent progress on nanomaterials with enzymatic activities, such as their synthesis and the regulation of their activity as well as their use in emerging biomedical fields, such as theranostics and bioorthogonal catalytic reactions.